2013
DOI: 10.4103/0019-5413.121577
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and safety of free-hand pedicle screw fixation in age less than 10 years

Abstract: Background:Pedicle screws are being used commonly in the treatment of various spinal disorders. However, use of pedicle screws in the pediatric population is not routinely recommended because of the risk of complications. The present study was to evaluate the safety of pedicle screws placed in children aged less than 10 years with spinal deformities and to determine the accuracy and complication (early and late) of pedicle screw placement using the postoperative computed tomography (CT) scans.Materials and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…This is particularly evident in the treatment of scoliosis in children, where the application is on the rise, and the age at which it is employed continues to decrease, allowing for more effective treatment interventions. This particular study [17] suggested that thoracic and/or lumbar pedicle screw fixation is a safe and effective approach for addressing a variety of spinal conditions in children under the age of 10. Moreover, research has demonstrated that when vertebral deformities are present, the likelihood of suboptimal screw placement is higher during free-hand screw insertion compared to cases involving normal vertebral bodies [18].…”
Section: Discussionmentioning
confidence: 92%
“…This is particularly evident in the treatment of scoliosis in children, where the application is on the rise, and the age at which it is employed continues to decrease, allowing for more effective treatment interventions. This particular study [17] suggested that thoracic and/or lumbar pedicle screw fixation is a safe and effective approach for addressing a variety of spinal conditions in children under the age of 10. Moreover, research has demonstrated that when vertebral deformities are present, the likelihood of suboptimal screw placement is higher during free-hand screw insertion compared to cases involving normal vertebral bodies [18].…”
Section: Discussionmentioning
confidence: 92%